2022
DOI: 10.1016/j.scitotenv.2021.151066
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of zinc-contaminated groundwater by iron oxide in situ adsorption barriers – From lab to the field

Abstract: Heavy metals such as zinc cannot be degraded by microorganisms and form long contaminant plumes in groundwater. Conventional methods for remediating heavy metal-contaminated sites are for example excavation and pump-and-treat, which is expensive and requires very long operation times. This induced interest in new technologies such as in situ adsorption barriers for immobilization of heavy metal contamination. In this study, we present steps and criteria from laboratory tests to field stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
5
17
0
Order By: Relevance
“…This kinetic study c adsorption of As(III) onto FeOOH coated sand was a multi-step process inv cal adsorption on the external surface and chemical binding with FeOOH re sand surfaces (chemical adsorption). This result agrees with previous lite outlines that the pseudo-second-order model represents a better adsorption The previous study revealed that the adsorption mechanism of arsenic on surface was a favorable chemical interaction between adsorbent and adsor permeable adsorptive barriers [12].…”
Section: Adsorption Kineticssupporting
confidence: 92%
See 4 more Smart Citations
“…This kinetic study c adsorption of As(III) onto FeOOH coated sand was a multi-step process inv cal adsorption on the external surface and chemical binding with FeOOH re sand surfaces (chemical adsorption). This result agrees with previous lite outlines that the pseudo-second-order model represents a better adsorption The previous study revealed that the adsorption mechanism of arsenic on surface was a favorable chemical interaction between adsorbent and adsor permeable adsorptive barriers [12].…”
Section: Adsorption Kineticssupporting
confidence: 92%
“…This result agrees with previous literature, which outlines that the pseudo-second-order model represents a better adsorption kinetic [12,15]. The previous study revealed that the adsorption mechanism of arsenic on a metal oxide surface was a favorable chemical interaction between adsorbent and adsorbate [11] and permeable adsorptive barriers [12].…”
Section: Adsorption Kineticssupporting
confidence: 92%
See 3 more Smart Citations